2019
DOI: 10.1111/1759-7714.13099
|View full text |Cite
|
Sign up to set email alerts
|

ACTH‐producing thymic neuroendocrine tumor initially presenting as psychosis: A case report and literature review

Abstract: A 32‐year‐old woman was referred to our hospital because of severe psychosis and was found to have an ectopic ACTH‐producing thymic neuroendocrine tumor. Laboratory data revealed an elevated serum cortisol and plasma ACTH level, hypokalemia, and metabolic alkalosis. Chest computed tomography (CT) revealed an anterior mediastinal mass and multiple pulmonary nodules. As the patient was unable to communicate because of her consciousness disturbance, she was managed with artificial ventilation and deep sedation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…Psychiatric complications can be observed in all forms of Cushing's syndrome (103,119,129,130,131) but seem to correlate with the intensity of hypercortisolism. Their prevalence is particularly high in patients with EAS (up to 50%, or even higher) (95,96,131). Various symptoms including depressive symptoms are very frequent in Cushing's syndrome, but intense hypercortisolism may also result in steroid psychosis.…”
Section: (H) Psychiatric Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric complications can be observed in all forms of Cushing's syndrome (103,119,129,130,131) but seem to correlate with the intensity of hypercortisolism. Their prevalence is particularly high in patients with EAS (up to 50%, or even higher) (95,96,131). Various symptoms including depressive symptoms are very frequent in Cushing's syndrome, but intense hypercortisolism may also result in steroid psychosis.…”
Section: (H) Psychiatric Complicationsmentioning
confidence: 99%
“…Various symptoms including depressive symptoms are very frequent in Cushing's syndrome, but intense hypercortisolism may also result in steroid psychosis. The clinical picture often associates agitation or paranoid symptoms, with or without delusional episodes (129,130,131,132,133). True melancholic syndromes, refractory to standard therapy, may also occur.…”
Section: (H) Psychiatric Complicationsmentioning
confidence: 99%
“…Symptoms and the degree of symptoms in patients with ectopic ACTH syndrome are related to cortisol levels, the histological type of the tumor, and tumor growth rate (8,9). It has been reported that some intrathoracic neuroendocrine tumors causing ectopic ACTH syndrome grow slowly, and the average interval between the onset of symptoms and clinical diagnosis is 3 years (10).…”
Section: Discussionmentioning
confidence: 99%
“…T h e e n d o c r i n o l o g i c a l d a t a a r e showed in Table 1. Blood routine: WBC 15.13×10 9 /L, N 12.66×10 9 /L, N 83.6%; fasting blood glucose 8.1 mmol/L, HbA1c 8.8%; potassium 3.3 mmol/L; thyroid function test: normal; magnetic resonance imaging (MRI) of the pituitary: the right pituitary gland is thinner than the left. Chest CT: A soft tissue density mass is seen next to the left mediastinum, with a maximum slice size of about 12.8 cm × 8.4 cm and a CT value of about 47 HU.…”
Section: Case Presentationmentioning
confidence: 99%
“…HGNECs are very difficult malignancies to diagnose due to the subtle presentation 1 . Ectopic adrenocorticotropic hormone (ACTH) secretion syndrome is a rare clinical manifestation, but is responsible for 15% of all cases of Cushing syndrome 4,5 . This has been previously well documented in the subset of small cell carcinoma of the lung, but not the pancreatic subset.…”
Section: Discussionmentioning
confidence: 99%